Effect of X-ray dose rates higher than 8 Gy/min on the functioning of cardiac implantable electronic devices. (7th April 2020) - Nakamura, Kazuhiko; Aoyama, Takahiro; Kaneda, Naoki; Otsuji, Masashi; Minami, Yoshitaka; Sakuragi, Ami; Nakamura, Masaru
Abstract: Direct irradiation may cause malfunctioning of cardiac implantable electronic devices (CIEDs). Therefore, a treatment plan that does not involve direct irradiation of CIEDs should be formulated. However, CIEDs may be directly exposed to radiation because of the sudden intrafractional movement of the patient. The probability of CIED malfunction reportedly depends on the dose rate; however, reports are only limited to dose rates ≤8 Gy/min. The purpose of this study was to investigate the effect of X-ray dose rates >8 Gy/min on CIED function. Four CIEDs were placed at the center of the radiation field and irradiated using 6 MV X-ray with flattening filter free (6 MV FFF) and 10 MV X-ray with flattening filter free (10 MV FFF). The dose rate was 4–14 Gy/min for the 6 MV FFF and 4–24 Gy/min for 10 MV FFF beams. CIED operation was evaluated with an electrocardiogram during each irradiation. Three CIEDs malfunctioned in the 6 MV FFF condition, and all four CIEDs malfunctioned in the 10 MV FFF condition, when the dose rate was >8 Gy/min. Pacing inhibition was the malfunction observed in all four CIEDs. Malfunction occurred simultaneously along with irradiation and simultaneously returned to normal function on stopping the irradiation. An X-ray dose rate >8 Gy/min caused a temporary malfunction due to interference. Therefore, clinicians should be aware of the risk of malfunction and manage patient movement when an X-ray dose rate >8 Gy/min is used for patients with CIEDs.